Optimising Leadership Style and Organisational Culture to Face Organisational Change in order to Support Human Resource Management in the Navy Environment - Ardi, Mahmud Ridho; Komaruddin, Komaruddin; Syafriady, Syafriady (AGUSPATI Research Institute, 2024)
— The Indonesian Navy faces challenges adjusting to environmental changes and increasingly complex tasks, where success depends on its Human Resources quality. Strategic, integrated and coherent HR management is required for the development and welfare of members. Autocratic leadership styles, common in the military, may increase efficiency but risk-reducing innovation and subordinate participation. In addition, an organisational culture increasingly influenced by globalisation has seen a decline in soldier discipline and morale. There are three main issues identified as obstacles to optimal leadership style and organisational culture to deal with organisational change in the context of human resource management in the Navy, namely the implementation of inappropriate leadership styles. The second issue is the shift in organisational cultural values within the Navy. The third issue is organisational change within the Navy, which must still be optimal. Formulating policies and strategies and comprehensive efforts to optimise the Navy's leadership styles and organisational culture is essential. A strategy is formulated to implement the policy, which will later be described in efforts that include changes in leadership style, improving organisational culture within the Navy and increasing organisational change.